2017
DOI: 10.4269/ajtmh.16-0721
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids and Lipoproteins During Uncomplicated Malaria: A Cohort Study in Lambaréné, Gabon

Abstract: Abstract. The serum lipid profile in malaria patients has been found to differ from that of healthy controls. We investigated serum lipid profile changes in malaria patients over time compared with patients with other febrile diseases. In total, 217 patients were included in the study (111 malaria patients and 106 symptomatic controls, defined as malaria-negative febrile patients). Serum lipid levels (mmol/L) were significantly lower in malaria patients compared with those with other febrile diseases (total ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
4
8
1
Order By: Relevance
“…Benjamin J et al in their study found that serum lipid levels (mmol/l) were significantly lower in malaria patients compared with those with other febrile diseases. 9 In present study mean value for total cholesterol was significantly lower in pf .malaria (151±12.83mg/dl) than in control group (182.64±12.08mg/dl) P-Value <0.05. Similarly serum HDL is significantly lower in pf malaria 29.39±5.66 mg/dl than in control group 40.4±3.29 mg/dl (P <0.05).…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Benjamin J et al in their study found that serum lipid levels (mmol/l) were significantly lower in malaria patients compared with those with other febrile diseases. 9 In present study mean value for total cholesterol was significantly lower in pf .malaria (151±12.83mg/dl) than in control group (182.64±12.08mg/dl) P-Value <0.05. Similarly serum HDL is significantly lower in pf malaria 29.39±5.66 mg/dl than in control group 40.4±3.29 mg/dl (P <0.05).…”
Section: Discussionsupporting
confidence: 39%
“…Benjamin J et al found that these result were consistent across their studies. 9 TG were raised in complicated than in healthy controls, but not statistically significant when compared to symptomatic control. As there was no significant difference in serum lipid between in healthy volunteers and non malarial febrile controls it is postulated that the changes in lipid profile in pf.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It was also reported that the extent of dyslipidemia is dependent on the severity of the disease [9,10]. Similar studies in both vivax and falciparum malaria patients reported that concentrations of HDL, LDL, and CHOL decreased significantly but TAGs increased in malaria-infected patients than in healthy control [11][12][13][14][15]. These reports generally support the opinion that malaria induces dyslipidaemia and hence, a good antimalarial agent should, in addition to clearing malaria parasite, restore homeostasis in lipid status.…”
Section: Introductionmentioning
confidence: 69%
“…These changes alter the erythrocyte's surface structure and contribute to the clinical manifestations of the disease [4][5][6][7] . Furthermore, people who become infected with P. falciparum parasites commonly develop decreased blood levels of low-density lipoprotein (LDL), high-density lipoprotein (HDL) and cholesterol 8,9 . Such alterations in blood constituents suggest that P. falciparum may use various lipid components in the blood, including lipoproteins, for its survival.…”
mentioning
confidence: 99%